Analisis Risiko Teknologi Informasi pada BANK ABC Menggunakan Framework ISO 31000 - Hagai Citra Christian; Melkior N.N. Sitokdana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Abstract ABC Bank is a company engaged in banking. Until now Bank ABC is still running. The company already has information technology or IT to support business activities within the company. Bank ABC uses the Mobile banking application, the function of the application is to provide convenience for customers in processing transactions in the form of bill payments, fund transfers, balance checks, making deposits anytime and anywhere via mobile phones or smartphones based on Android or IOS (iPhone Operating System. However, it is undeniable that there will be possible risks that can occur in m-Banking to disrupt existing business process activities. For this reason, it is very important to know the risks that can have an impact on the performance of m-Banking. The author uses the ISO 31000 framework as a tool to minimize the risks that exist in m-Banking. Keywords— ISO 31000, risk analysis, risk treatment